Intersecting paths: A rare case report of malignant melanoma in a patient with body dysmorphic disorder (Journal of Ideas in Health, 2023)
Background: Body dysmorphic disorder (BDD) characterized by excessive and persistent preoccupation with perceived defects or flaws in appearance and has a prevalence of 1.7-2.9%. It is a disorder with a relatively unclear etiology.Case presentation: A 36-year-old unmarried female presented to the surgery department with a self-inflicted lesion on her right ankle. The patient underwent fine needle aspiration cytology, and later, a wide local excision of the lesion was done. The final histological diagnosis of malignant melanoma was established. On careful psychiatric evaluation, the patient had an excessive and persistent preoccupation with her appearance, which caused severe psychological and social morbidity and drove her to her actions. Thus, the final diagnosis of body dysmorphic disorder (DSM V) was established. The patient was put on Fluoxetine and cognitive behavioral therapy.Conclusion: Given the significantly reduced functionality and quality of life, BDD should be recognized and accurately diagnosed.